Adsorption of Cadmium from Aqueous Solutions Using Low cost Materials-A Review - Padmaja, M.; Bhavani, R.; Pamila, R. (International Journal of Engineering and Technology, 2018)
With the onset of industrialization, a lot of anthropogenic sources of cadmium, including industrial emissions, application of fertilizers and sewage sludge to farm land has lead to the contamination of water bodies, and has increased cadmium uptake by agricultural crops, grown for human consumption. Cadmium when present, even at low concentrations may pose serious health as well as environmental hazards. The use of various materials has been widely investigated as a replacement of recent expensive methods for removing cadmium from water and wastewater. Plant based natural materials, agricultural products, nano materials and industrial wastes are efficiently used as low-cost adsorbents. Until now, most of the researchers have attempted to review the literature for multiple heavy metals. In the current review, an elaborate list of literature has been compiled to provide information on a wide range of natural as well as modified adsorbent materials for the removal of Cadmium from wastewater.